Analisis Pemberian Reward dan Pengaruhnya terhadap Motivasi Belajar Siswa Sekolah Dasar: Analysis of Reward Giving and Its Influence on Elementary School Students' Learning Motivation - Mujahidah, Nida (FAI UIM, 2023)
The purpose of this study was to determine the effect of giving rewards on students' learning motivation. This study is an experimental study with a quantitative approach. The type of research is a true experiment with a research design in the form of Pretest-Posttest Control Group Design. The research stage is through pre-nontest, treatment, and post-nontest. The population in this study were all fourth-grade students of Muhammadiyah 12 Pamulang Elementary School, South Tangerang, Banten, totaling 36 students. The sample was class IV A as an experimental class with 18 students and class IV B as a control class with 18 students. The sampling technique used purposive sampling, research data were obtained through questionnaires and observation sheets. The data analysis techniques used were descriptive statistics and inferential statistics. The results of the data analysis showed that there was an effect of giving rewards on students' learning motivation, as well as a significant difference in the probability value between the experimental class and the control class. The form of reward given was verbal and nonverbal.